PENGEMBANGAN WEBSITE TOKO ONLINE DENGAN MENGGUNAKAN METODE CROSS SELLING PADA FSP SHOP SURABAYA - Setiawan, Citra; Ayuningtyas, Ayuningtyas; Susilo, Tegar Heru (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Abstract:Friendship (FSP) Shop is a store operations located in Central Semampir Street Gang 6/6 - 60 213 Surabaya East Java. FSP Shop sells a variety of apparel products for youngsters such as clothes (shirts and T-shirts), jeans, jackets and accessories (slayer, hats, etc.). Sales made by the FSP Shop is currently done by through the online store website. User or users of the website include online store owner as admin and customer FSP Shop itself. For now, the sales website used by FSP Shop is still very modest in which only covers the sale process only. The website does not focus on the interests and customer satisfaction is evident with no variations in supply and service to customers. It has an impact on sales of the clothing store business into the future, allowing the loss of customer loyalty, and lead customers do not want to shop again at the store. Besides these two problems, FSP Shop himself wished to increase the number of sales of each item in the future as well as continue to maintain customer loyalty.From the above problems, website development FSP Shop online store today with the adoption of cross selling. Cross selling is a suggestion that is obtained based on the data transaction history. Cross selling is also capable of determining other products which could be sold as well.Based on the results of trials that have been done by the FSP Shop, then the application can generate an output display for information on cross selling products that can be used as a recommendation. Keywords: Website, Online Store, Cross SellingPENGEMBANGAN WEBSITE TOKO ONLINE DENGAN MENGGUNAKAN METODE CROSS SELLING PADA FSP SHOP SURABAYA